OBE System Explanations – An Implementation of Cognitive Domain on Theory Course - Md. Foisal Haque (Sinergi International Journal of Education, 2025)
This research explains the OBE (Outcome-Based Education) system by implementing cognitive domain levels in the geotechnical engineering theory course. For this reason, the two program outcomes (POs) are proposed to evaluate the performance of students by achieving the threshold value of course outcome (TVCO) to obtain marks of individual course outcome (CO) considered for the mid-term and final exams. The minimum 70 % mark obtained in an individual CO is considered for achieving the TVCO according to the grade point values of the grading system. Most students are not achieving TVCO because of improper knowledge of pre-requisite courses, the lower voice of the teacher, absent minds of students during class, lack of practice on complex problems at home, etc. So, some remedial measures are taken to overcome these limitations such as mandatory to compete for the pre-requisite courses before taking the relevant higher level course, using a mouth-piece to increase the voice of the teacher, sharing some interesting issues with students to remove absent mind, try to more practice by proper utilizing time in home, etc. However, there is a scope to enhance this research in the future by applying other domains of the OBE system to the theory and lab courses.